Independensi Penuntutan Perkara Koneksitas Ditinjau dari Peraturan Presiden Nomor 15 Tahun 2021 Tentang Organisasi dan Tata Kerja Kejaksaan - Nofia Sari, Okta; Arfiani, Nur; Mustofa, Mustofa (WELFARE STATE Jurnal Hukum, 2023)
In Article 89 paragraph 1 of the Criminal Procedure Code it is stated that "criminal acts committed jointly by those belonging to the general court environment and the military court environment, are examined and tried by courts within the general court environment unless according to the decision of the Minister of Defense and Security with the approval of the Minister of Justice, the case must be examined and tried by a court within the military court environment”. In this case, it is necessary to increase the effectiveness of the implementation of the duties and powers of the Attorney General's Office of the Republic of Indonesia in carrying out technical coordination of prosecutorial prosecution and handling of connected cases and the application of the principles of embodiment of bureaucratic reform and the acceleration of the provision of legal services to the public by appointing a Junior Attorney General for Military Crime in the structure the Attorney General's Office. the existence of Presidential Decree Number 15 of 2021 is intended to accelerate the handling of connectivity cases. However, competent human resources are needed to run this structure as well as budget allocations for military members who fill these positions.